Safety of biotechnological crops and foods, “20 years of marketing” - Garro-Monge, Giovanni (2017)
Biotechnology has been used for thousands of years to obtain benefits for humans. Long before humans have used techniques such as hybridization, mutagenesis and polyploidy, generating changes at the genetic level to obtain desirable characteristics is now possible to use genetic engineering to modify or transfer genes from one organism to another in order to obtain products with certain advantages over its conventional counterpart. Genetic engineering techniques were started 30 years at the level of research and 20 years ago products are marketed on a large scale by these them. Although they are a number of comments regarding their safety and biosecurity by certain sectors of society to date multiple studies with great scientific support around the world conclude generally, that environmental and human health level, not there are differences between conventional breeding and improvement by genetic engineering. The crops and food improvement through biotechnology is accompanied by standards and regulatory biosafety frameworks, which involve risk analysis with long-term tests to ensure food safety.